Smart meter-tnb dual tariff for domestic application - Nasyrah, Abdul Rahim (2012)
Presently, the usage of electricity is not balanced between day and night. High demand from industrial, commercial and even residential at day time contributed to extra power generation by Tenaga Nasional Berhad (TNB). Some of these generations’ resources, such as coal need all-time non-stop burning process. Due to this, there will be some wastage of energy at night time. This study proposes dual tariff electricity for domestic usage. Tariff will be divided into two which is peak time and off-peak time. Off-peak time will have lower tariff compare to peak time. Today, domestic area is using the typical energy meter, which only applicable for single tariff. To apply dual tariff, a new meter should be used; Smart Meter for Dual Tariff. This meter work as same as TNB energy meter, but it displays the energy usage for peak time and off-peak time. There are two LED to indicate peak time and off-peak time. The meter has select button to display important information, either energy usage, bill or tariff. The development of the meter consists of the reverse-engineering of typical energy meter, the separate energy accumulation for peak and off-peak and the display as interface.